The Effect of Work Life Balance on Female Employee Loyalty - Fina Juliana; Arbani Fitriani (The Future of Education Journal, 2026)
The increase in female employees in the workforce is accompanied by demands as workers as well as demands in their personal lives. This condition creates an imbalance between work and personal life that can affect female employees' loyalty to the company. This study aims to examine the effect of work-life balance on female employee loyalty. This study uses a quantitative approach with a causal type. The sampling technique used non-probability sampling, and data analysis was performed using simple linear regression. The sample consisted of 111 female employees. The employee loyalty scale referred to Huda's (2020) measurement tool based on Chen et al.'s (2002) theory, and the work-life balance scale was based on Fisher et al.'s (2009) theory. The validity results of the study with a corrected item-total correlation value on the employee loyalty scale of 0.431-0.853 and reliability of 0.950, the work-life balance scale of 0.414-0.853 and a reliability value of 0.930. The results showed a significant positive influence between work-life balance and employee loyalty (r = 0.568; p < 0.05), meaning that the higher the work-life balance, the higher the loyalty. The coefficient of determination (R²) value is 0.323, which means that work-life balance contributes 32.3%, while the remaining 67.7% is influenced by other factors.